INTERACTION OF SILVER NANOPARTICLES WITH VANCOMYCIN: AN UV-VIS STUDY - BALINT, Reka; PALTINEAN, Gertrud Alexandra; MOCANU, Aurora; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Silver nanoparticles (AgNPs) were synthesized by chemical reduction method, using different reducing systems. The interaction of AgNPs and vancomycin hydrochloride (V) was investigated by UV-Vis spectroscopy, and their tendency to form AgNP@V associations or complexes was identified in colloidal solutions. Moreover their affinity to self-assembly and aggregate is also examined. This behavior is important and decisively influences the antimicrobial effect of AgNP@V complexes.